A Study of Chinese Language Learning Problems of Thai Students: A Case Study of Reduplication of Chinese Adjectives: ไวยากรณ์ภาษาจีนกลาง, คำคุณศัพท์ที่อยู่ในรูปคำซ้ำ - ประภากร ภูเทพ (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2019)
The present study aimed to investigate the teaching problem in Mandarin Chinese grammar focusing on studying reduplication of Chinese adjectives. The participants were divided into two groups. The first group were 50 Thai students studying Mandarin Chinese at People’s Republic of China and the second group were 50 Thai students studying Mandarin Chinese in Thailand. The research instruments used were a questionnaire and comprehension test about the reduplication of Chinese adjectives which consisted of three main parts – patterns of the reduplication, rules of Mandarin Chinese grammar and its implementation. The study revealed that both groups of the students had the same problems which were the implementation of the reduplication to construct sentences and using it in real-life communication. Besides, rules of Mandarin Chinese grammar and patterns of the reduplication were also obstacles for the students. The main reasons of these obstacles were an insufficiency of real-life communication outside classroom and also teaching technique which redundantly focused on remembering grammar rules. The study also suggested that teachers should seek for more appropriate method to teach Mandarin Chinese grammar for Thai students in order to reduce students’ language error. Moreover, using role play in classroom is the alternative way that helps students engage to a real-life interaction and it can be used as a tool to reflect students’ thought to use language in an appropriate context.